Employee Performance from an Organizational Culture Perspective at PT Tri Stuba Amiga Bandung - Marsa Velma Marcellama; Silmi Madinah Fadzri (Publikasi Inspirasi Indonesia, 2026)
This article aims to explore the perspectives of organizational culture and work discipline on employee performance through a qualitative method using a literature review approach. The focus of this article is on data and results from previous research at PT Tri Stuba Amiga in Bandung. Unlike the original quantitative study, this article seeks to analyze more concisely and in-depth how these two factors interact in shaping work performance. The method used was a qualitative descriptive approach based on secondary data analysis. Through a literature review of previous study results, it was found that organizational culture plays a dominant role (contributing 73.3%) in shaping employee behavior, while work discipline serves as a crucial supporting factor. The analysis concluded that reinforcing organizational values, balanced with consistently high discipline, has a positive and significant impact on the achievement of corporate goals. This article is intended to provide a more practical perspective for corporate management in managing human resources.